TO RECONSIDER THE “ACONTECERES”, TO RECONSIDER THE SPACES IN CHILE. - Onetto Pavez, Mauricio (Revista de Historia Social y de las Mentalidades, 2024)
The object of this article is to reflect on the theoretical perspectives and main lines of analyses that the editors of the dossier had in mind in order to create this project. The first part will focus on the importance of the relationshihbetween “space”, history and memory by generally explaining the significance of this correspondence for the topics of the dossier. The second part will present the main motivations that arise for studying the Chilean case.